Nanometer size silicon particles for hyperpolarized MRI - Grzegorz Kwiatkowski (Nature Portfolio, 2017)
Abstract Hyperpolarized silicon particles have been shown to exhibit long spin-lattice relaxation times at room temperature, making them interesting as novel MRI probes. Demonstrations of hyperpolarized silicon particle imaging have focused on large micron size particles (average particle size (APS) = 2.2 μm) as they have, to date, demonstrated much larger polarizations than nanoparticles. We show that also much smaller silicon-29 particles (APS = 55 ± 12 nm) can be hyperpolarized with superior properties. A maximum polarization of 12.6% in the solid state is reported with a spin-lattice relaxation time of 42 min at room temperature thereby opening a new window for MRI applications.